The impact of preconditioning strategies designed to improve 2000-m rowing ergometer performance in trained rowers: A systematic review and meta-analysis - Turnes, T.; Cruz, R. S. O.; Caputo, F.; De Aguiar, R. A. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The 2000-m rowing-ergometer test is the most common measure of rowing performance. Because athletes use different intervention strategies for enhancing performance, investigating the effect of preconditioning strategies on the 2000-m test is of great relevance. This study evaluated the effects of different preconditioning strategies on 2000-m rowing-ergometer performance in trained rowers. Methods: A search of electronic databases (PubMed, Google Scholar, and Web of Science) identified 27 effects of different preconditioning strategies from 17 studies. Outcomes were calculated as percentage differences between control and experimental interventions, and data were presented as mean?±?90% confidence interval. Performance data were converted to the same metrics, that is, mean power. Meta-regression analyses were conducted to assess whether performance level or caffeine dose could affect the percentage change. Results: The overall beneficial effect on 2000-m mean power was 2.1% (90% confidence limit [CL] ±0.6%). Training status affected the percentage change with interventions, with a -1.1% (90% CL ±1.2%) possible small decrease for 1.0-W·kg-1 increment in performance baseline. Caffeine consumption most likely improves performance, with superior effect in higher doses (=6 mg·kg-1). Sodium bicarbonate and beta-alanine consumption resulted in likely (2.6% [90% CL ±1.5%]) and very likely (1.4% [90% CL ±1.2%]) performance improvements, respectively. However, some preconditioning strategies such as heat acclimation, rehydration, and creatine resulted in small to moderate enhancements in 2000-m performance. Conclusions: Supplementation of caffeine and beta-alanine is a popular and effective strategy to improve 2000-m ergometer performance in trained rowers. Additional research is warranted to confirm the benefit of other strategies to 2000-m rowing-ergometer performance.